Pengaruh Teknologi Informasi, Kesadaran Wajib Pajak, Efektivitas Pemungutan Pajak Terhadap Kemandirian Fiskal Daerah - Adzanu, Luthfi; Moh. Yuddy Yudawirawan (EkoPreneur, 2025)
This study aims to obtain empirical evidence regarding the effect of audit report lag, audit reputation, and audit tenure on the acceptance of going concern audit opinions in companies operating in the consumer non-cyclical sector and listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research population consisted of 125 companies, and through a purposive sampling technique based on predetermined criteria, 39 companies were selected as the sample. With an observation period of five consecutive years, the total number of data analyzed amounted to 195. The data used in this study were secondary data derived from audited financial statements and annual reports published by each company. Logistic regression analysis was applied as the primary analytical method, with the support of E-Views 12 software. The findings of this study indicate that, simultaneously, audit report lag, audit reputation, and audit tenure influence the likelihood of a company receiving a going concern audit opinion. However, the results of the partial test show different effects. Audit report lag does not have a significant effect on the acceptance of going concern audit opinions, suggesting that delays in audit completion do not directly determine the auditor’s assessment of business continuity. Similarly, audit reputation does not significantly affect the issuance of going concern opinions, implying that the credibility or prestige of an audit firm alone is not a determining factor. In contrast, audit tenure has a significant effect, indicating that the length of the auditor’s engagement with a company plays an important role in shaping the auditor’s judgment regarding going concern issues. These results provide valuable insights for auditors, regulators, and stakeholders in assessing the factors influencing the issuance of going concern audit opinions.   Keywords: Going Concern Audit Opinion, Audit Report Lag, Audit Reputation, Audit Tenure